Teenager’s Thought is Related to Self-Control in Safe Smartphone Use During the Covid-19 Pandemic - Rizki Fitryasari; Rr Dian Tristiana; Ah Yusuf (Journal of Global Pharma Technology, 2020)
Introduction: The use of smartphones in the Covid-19 pandemic era is an inevitable phenomenon, including for teenager who participated in online learning. The inability to control themselves independently in using smartphone-based devices is a risk factor for gadget addiction. This study aimed to analyze the relationship between teenagers' thoughts and self-control in safe smartphone use in the Covid-19 pandemic era. Methods: This study was a descriptive correlation design based on a cross-sectional approach. The population was teenagers aged 11-18 years in Surabaya, Indonesia who had participated in online learning during the Covid-19 pandemic. The purposive sampling was conducted and gained 185 respondents. The study variables were teenagers' thoughts and self-control in using smartphones. The instrument used was a questionnaire and the data were analyzed using the Spearmen Rank test. Results: The statistical test results showed that a good thought of teenagers was related to high self-control in using a smartphone (p = 0.000, r =0.371). Conclusion: The teenager’s thought in smartphone usage was formed based on benefits, barrier, beliefs, and the consequences of online learning activities. The teenagers’ awareness will lead to a good self-control for limiting the smartphones usage independently. Further research should be focused on the development of a safe smartphone usage guidance that can assist teens to be able to use the smartphone safely.